Using the Consolidated Framework for Implementation Research to examine implementation determinants of specialty mental health probation - Tonya B. Van Deinse; Alicia Bunger; Stacey Burgin; Amy Blank Wilson; Gary S. Cuddeback (Health & Justice, 2019)
Abstract Background Specialty mental health probation (SMHP) is designed to improve outcomes for the large number of people with serious mental illnesses who are on probation and/or parole. The evidence for specialty mental health probation is promising; however, little is known about the implementation challenges and facilitators associated with SMHP. To address this gap, we used the consolidated framework for implementation research (CFIR) to analyze 26 interviews with stakeholders representing multiple agencies involved in the implementation of SMHP. Results Results indicate a number of challenges and facilitators related to the inner setting, outer setting, implementation process, and characteristics of individuals. Conclusions Findings suggest that complex and cross-sectoral interventions are context-dependent and introduce a number of challenges and facilitators related to multiple CFIR domains. Consequently, agency administrators implementing these types of interventions should consider small pilot studies and develop implementation strategies tailored to the local implementation context.